A price for flexibility? The temp agency wage gap in Sweden 1998 - 2008 - Pernilla Andersson Joona; Eskil Wadensjö (Institute for the Study of Labor (IZA), 2012)
Temporary agency employment has grown rapidly in Sweden as in many other countries. The sector was deregulated in the early 1990s and there are now only few remaining restrictions. Even though there are collective agreements covering a large part of the workers in the sector, the unions are worried about low wages and poor working conditions in the sector. This paper analyzes the development of the temporary agency wage gap during the period 1998-2008 using Swedish register data. We find that from a nearly non-existent gap in 2001 and a positive wage gap for women, both male and female temp agency workers received between 16 and 18 percent lower wages in 2008. This development appears partly to be explained by a lower return to university education among temp agency workers than among those employed in other sectors.
urn:nbn:de:101:1-201303202224
Keywords: J31; J42; J62; 330; temporary agency employment; wages; Leiharbeit; Lohnstruktur; Niedriglohn; Arbeitsmarktflexibilität; Schweden